The Effect Of Cucumber Juice On Hypertension On Menopaused Mothers Aged 50-60 Years In Mawar Hamlet Jatirejo Village Pagar Merbau District Lubuk Pakam Regency Year 2022 - Yessy Arisman; Cindy .; Reni Novia (JURNAL KEBIDANAN KESTRA (JKK), 2023)
Hypertension is the highest cause of mortality and morbidity in Indonesia. Non-pharmacological therapy that can reduce blood pressure in patients with hypertension is cucumber juice . The purpose of this study was to compare the effect of 100gr and 200gr cucumber juice on hypertension in post menopausal women aged 50-60 years in Mawar Hamlet, Jatirejo Village in 2022.study used a quasi-experimental research design with a non-equivalent control group design approach . The population in this study were all women with hypertension, totaling 40 mothers. The samples obtained were 28 mothers with purposive sampling technique . The statistical test used was the paired T-Test with a 95% confidence level (? = 0.05).The results of the Paired T-Test in the control group showed a p-value of 0.010 <0.05, meaning that there was an effect of giving 100gr of cucumber juice on systolic blood pressure and a p-value of 0.007 <0.05, meaning that there was an effect of giving 100gr of cucumber juice on diastolic blood pressure. The results of the Paired T-Test showed a p-value of 0.000 <0.05, meaning that there was an effect of giving 200gr of cucumber juice on systolic blood pressure, and a p-value of 0.000 <0.05, meaning that there was an effect of giving 200gr of cucumber juice on diastolic blood pressure.There is influence Among group treatment and group control to change pressure blood however group treatment more effective for lower pressure blood on sufferer hypertension in hamlet Rose Village Jatirejo 2022 .